Estimation of delivered dose to lung tumours considering setup uncertainties and breathing motion in a cohort of patients treated with stereotactic body radiation therapy. (August 2021) - Karlsson, Kristin; Lax, Ingmar; Lindbäck, Elias; Grozman, Vitali; Lindberg, Karin; Wersäll, Peter; Poludniowski, Gavin
Highlights: Estimation of delivered dose to lung tumours in SBRT considering geometrical errors. Quantitative estimates, on statistical basis, of delivered tumour dose. Estimation of difference between two IGRT methods extensively used in SBRT. Illustration of a framework for carrying out estimates of delivered dose. Online cone-beam CT image-guidance typically leads to higher tumour dose. Abstract: Introduction: Dose-response relationships for local control of lung tumours treated with stereotactic body radiotherapy (SBRT) have proved ambiguous, however, these have been based on the prescribed or planned dose. Delivered dose to the target may be a better predictor for local control. In this study, the probability of the delivered minimum dose to the clinical target volume (CTV) in relation to the prescribed dose was estimated for a cohort of patients, considering geometrical uncertainties. Materials and methods: Delivered doses were retrospectively simulated for 50 patients treated with SBRT for lung tumours, comparing two image-guidance techniques: pre-treatment verification computed tomography (IG1) and online cone-beam computed tomography (IG2). The prescribed dose was typically to the 67% isodose line of the treatment plan. Simulations used in-house software that shifted the static planned dose according to a breathing motion and sampled setup/matching errors. Each treatment was repeatedly simulated, generating a multiplicity of dose-volume histograms (DVH). From these, tumour-specific and population-averaged statistics were derived. Results: For IG1, the probability that the minimum CTV dose ( D 98% ) exceeded 100% of the prescribed dose was 90%. With IG2, this probability increased to 99%. Conclusions: Doses below the prescribed dose were delivered to a considerably larger part of the population prior to the introduction of online soft-tissue image-guidance. However, there is no clear evidence that this impacts local control, when compared to previous published data.